Human African trypanosomiasis control: Achievements and challenges. - Serap Aksoy; Phillipe Buscher; Mike Lehane; Philippe Solano; Jan Van Den Abbeele (Public Library of Science (PLoS), 2017)
Sleeping sickness, also known as human African trypanosomiasis (HAT), is a neglected disease that impacts 70 million people living in 1.55 million km2 in sub-Saharan Africa. Since the beginning of the 20th century, there have been multiple HAT epidemics in sub-Saharan Africa, with the most recent epidemic in the 1990s resulting in about half a million HAT cases reported between 1990 and 2015. Here we review the status of HAT disease at the current time and the toolbox available for its control. We also highlight future opportunities under development towards novel or improved interventions.